Enhanced antioxidant activity of brown seaweed Laminaria japonica by fermentation using isolated Bacillus subtilis - Yueh-Hao Ronny Hung; Ya-Han Chang; Hsuan-Ju Lin; Li-Ho Chiang; Hong-Ting Victor Lin (Bioresources and Bioprocessing)
Abstract Bioactive compounds from the brown seaweed Laminaria japonica have received considerable attention from the food industries to explore their biological activities. However, effectively producing bioactive compounds from seaweed requires further investigation because of the complex composition of seaweed cell walls. In the present study, Bacillus subtilis strains were isolated and screened for the production of extracellular hydrolytic enzymes for the fermentation of L. japonica to enhance its antioxidant activity. Three B. subtilis strains were successfully isolated from commercial natto products, and their hydrolytic abilities were evaluated using fibrinogen, alginate, and cellulose plates. Strain B2 exhibited great application potential in degrading seaweed cell wall polysaccharides compared with other strains. Subsequently, strain B2 was utilized for seaweed fermentation, and chemical composition alterations (including phenolic compounds, total sugar, and reducing sugar) of the fermented broth were analyzed. A high sulfate content was detected in the polysaccharide fraction of the fermented seaweed. Finally, the antioxidant activities (ferrous iron-chelating ability, reducing power, ABTS radical-scavenging ability, and DPPH radical-scavenging ability) of the supernatant, polysaccharide, and polyphenol fractions from the fermented seaweed were assessed and compared with those of the nonfermented groups. Results indicated that fermentation with B. subtilis could enhance the antioxidant activity in supernatant, polysaccharide, and polyphenol fractions. Fermentation acted positively on the bioconversion of L. japonica extract, thereby improving the antioxidant properties. Overall, this study provides valuable insights into enhancing the antioxidant activities of L. japonica through fermentation.